Determinants of foreign direct investment from EU-15 Countries in Poland - Andrzej Cieślik (Central European Economic Journal (CEEJ), 2019)
During the last two decades, Poland has become a large recipient of inward foreign direct investment (FDI). This article uses standard panel data techniques to study empirically the determinants of inward FDI in Poland during the period 1996-2015 made by multinational enterprises coming from the old European Union (EU)-15 member states. The estimated specification is derived from the knowledge-capital (KC) model and includes two types of capital: human and physical. The assembled empirical evidence points to the horizontal motive as the primary reason for undertaking FDI in Poland by multinational firms based in the old EU-15 member states. Moreover, the KC model does not seem to explain better the pattern of inward FDI in Poland compared to the standard ad hoc gravity model of international capital mobility.
Keywords: F23; P33; 330; factor endowments; foreign direct investment; EU-15 member states; panel data analysis; Poland